بررسی ترالی های اورژانس مرکز آموزشی درمانی امام خمینی(ره) ارومیه - Shokohi, Shahram; Aghdashi, Mir Mousa (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2025)
Background: Cardiopulmonary arrest is a life-threatening event that, if not managed promptly, leads to death or irreversible permanent complications. To enable rapid and effective action during cardiopulmonary arrest, an emergency trolley or crash cart has been designed with the purpose of providing all tools, equipment, and medications required for timely and effective intervention. This study was conducted to evaluate the level of preparedness of emergency trolleys in different wards of Imam Khomeini Educational–Therapeutic Center of Urmia University of Medical Sciences and to compare their status with national standards and guidelines. Materials and Methods: This descriptive study was carried out after approval by the Research Council of Urmia University of Medical Sciences. First, all emergency trolleys in all wards of Imam Khomeini Educational–Therapeutic Center in Urmia were identified. Then, using the Ministry of Health and Medical Education’s directive regarding drug items, available equipment, type of trolley, location, and periodic control, each trolley was evaluated and compared with national standards. Results: A total of 38 emergency trolleys in this center were examined. Of these, 25 trolleys (65.8%) were located in easily accessible areas. Twenty-seven trolleys (71.1%) were equipped with a DC shock device mounted on the trolley. Twenty-four trolleys (42.1%) had an oxygen cylinder, and only 50% of these cylinders were full. Daily periodic control was performed in 86.8% of cases. In none of the trolleys were the non-drug consumable items completely consistent with national standards. Discussion and Conclusion: In the present study, many of the evaluated variables did not conform to the standards issued by the Ministry of Health. Some deficiencies—such as the absence of oxygen cylinders and DC shock devices on the trolleys—represent critical shortcomings. While the medications and consumables present generally followed the directive, the number of items actually checked did not comply with the recommended checklist. Failure to regularly control drugs, tools, equipment, and consumable supplies on the trolley can render resuscitation efforts ineffective or cause delays in cardiopulmonary resuscitation, leading to irreversible harm to patients in critical conditions. چکيده: ایست قلبی-ریوی یکی از حوادث تهدید کنندة حیات بیماران است که در صورت عدم اقدام به موقع، مرگ یا عوارض دائم غیر قابل برگشت در پی خواهد داشت.به منظور اقدام بلادرنگ و موثر هنگام ایست قلبی-ریوی وسیله ای به نام ترالی اورژانس یا ترالی احیا با هدف تامین ابزارها ،وسایل و داروهای مورد نیاز جهت مداخله سریع و موثرطراحی شده است.با هدف ارزیابی میزان آمادگی ترالی های اورژانس مستقر در بخشهای مختلف مرکز آموزشی درمانی امام خمینی دانشگاه علوم پزشکی ارومیه، و مقایسه آن با استانداردها و دستور العملهای کشوری، پژوهش حاضر طراحی و اجرا گردید. روش کار:این مطالعه بصورت توصیفی و پس از تصویب در شورای پژوهشی دانشگاه علوم پزشکی ارومیه اجرا شد. ابتدا تمامی ترالی های اورژانس در تمامی بخشهای مرکزآموزشی درمانی امام خمینی (ره) ارومیه شناسایی و سپس با استفاده از دستورالعمل وزارت بهداشت و درمان در خصوص اقلام دارویی، تجهیزات موجود، نوع ترالی، محل استقرار و کنترل های دوره ای با استاندارد کشوری مقایسه گردید. یافته ها: 38 ترالی موجود در این مرکز مورد بررسی قرار گرفتند. از این تعداد 25 عدد (8/65%) در محل قابل دسترسی قرار داشتند. 27 ترالی(1/71%) مجهزبه دستگاه DC شوک بر روی ترالی بودند. 24 ترالی (1/42%) دارای کپسول، بوده و فقط 50% از این کپسولها پر بودند (19).کنترل دوره ای روزانه، در 8/86% موارد انجام میشد.در هیچیک از ترالی های مورد بررسی ، اقلام مصرفی غیر دارویی بطور کامل مطابق با استاندارد کشوری نبودند. بحث و نتیجه گیری:در مطالعه حاضر، تعداد زیادی از متغییرهای مورد پژوهش با استاندادهای ابلاغی وزارت بهداشت همخوانی نداشتند.پاره ای از نواقص از جمله نبود کپسول اکسیژن و دستگاه DC شوک در ترالی ها نقصهای بسیار حیاتی هستند. اقلام دارویی و مصرفی موجود مطابق با دستورالعمل بودند ولی تعداد اقلام مورد بازبینی، مطابق دستور العمل نبودند. عدم کنترل منظم داروها، ابزارها،تجهیزات و وسایل مصرفی ترالی میتواند اقدامات احیا را غیر موثر نموده و یا سبب تاخیر در احیای قلبی-ریوی و آسیبهای جبران ناپذیر به بیمار در شرایط بحرانی شود. کلیدواژه ها: ایست قلبی- ریوی، احیای قلبی - ریوی،ترالی اورژانس